2022
DOI: 10.1007/s00210-022-02360-x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital and laboratory outcomes of patients with COVID-19 who received vitamin D supplementation: a systematic review and meta-analysis of randomized controlled trials

Abstract: Coronavirus disease 2019 (COVID-19) has a wide-ranging spectrum of clinical symptoms, from asymptomatic/mild to severe. Recent research indicates that, among several factors, a low vitamin D level is a modifiable risk factor for COVID-19 patients. This study aims to evaluate the effect of vitamin D on hospital and laboratory outcomes of patients with COVID-19.Five databases (PubMed, Embase, Scopus, Web of Science, and Cochrane Library) and clinicaltrials.gov were searched until July 2022, using relevant keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Recent meta-analysis has described the direct role of vitamin D in reducing the severity of COVID-19. Zaazouee et al [46] showed that vitamin D supplementation in patients with COVID-19 significantly decreased rates of intensive care admissions compared with controls. Similar results were reported by Feiner-Solis et al [47], and cross-sectional case-control and longitudinal studies have also demonstrated that higher levels of vitamin D were associated with a reduction in COVID-19 risk and severity [48].…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analysis has described the direct role of vitamin D in reducing the severity of COVID-19. Zaazouee et al [46] showed that vitamin D supplementation in patients with COVID-19 significantly decreased rates of intensive care admissions compared with controls. Similar results were reported by Feiner-Solis et al [47], and cross-sectional case-control and longitudinal studies have also demonstrated that higher levels of vitamin D were associated with a reduction in COVID-19 risk and severity [48].…”
Section: Discussionmentioning
confidence: 99%
“…One showed that admissions to intensive care were reduced but with no other benefit. 19 The other showed a beneficial trend but no improvement in clinical outcomes. 20 ESCMID looked at several other freely available drugs or treatments that had achieved near-mythical status despite showing no antiviral activity.…”
Section: Prophylaxis and Treatmentmentioning
confidence: 94%
“…Two major meta‐analyses arrived at different conclusions. One showed that admissions to intensive care were reduced but with no other benefit 19 . The other showed a beneficial trend but no improvement in clinical outcomes 20 …”
Section: Prophylaxis and Treatmentmentioning
confidence: 99%
“…In contrast to preventive lower dose supplementation, clinical intervention trials with higher doses of vitamin D in hospitalized COVID-19 patients revealed some positive meta-analytical evidence especially on the risk for ICU admission [ 83 , 85 , 91 , 92 , 93 ] although not all meta-analyses showed significant beneficial effects [ 87 , 89 ] ( Table 1 ). In addition, it is suggested that COVID-19 patients may rather benefit from receiving a daily or maintained in time vitamin D dose in contrast to a single vitamin D dose, which does not seem to have any effect on the health status of the patients studied [ 121 , 122 ].…”
Section: Selected Nutrients and Covid-19mentioning
confidence: 99%